2020
DOI: 10.3390/ma13194238
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics of Controlled Low-Strength Materials with Waste Paper Sludge Ash (WPSA) for Prevention of Sewage Pipe Damage

Abstract: In this study, the effects of the mixing conditions of waste paper sludge ash (WPSA) on the strength and bearing capacity of controlled low-strength material (CLSM) were evaluated, and the optimal mixing conditions were used to evaluate the strength characteristics of CLSM with recyclable WPSA. The strength and bearing capacity of CLSM with WPSA were evaluated using unconfined compressive strength tests and plate bearing tests, respectively. The unconfined compressive strength test results show that the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…It was found that CLSM with WPSA performed better as backfill and was more stable than soil immediately after construction. The results of this study confirm that CLSM with WPSA can be utilized as sewage-pipe backfill material [ 39 ].…”
Section: Description Of the Articles Presented In The Issuesupporting
confidence: 74%
See 1 more Smart Citation
“…It was found that CLSM with WPSA performed better as backfill and was more stable than soil immediately after construction. The results of this study confirm that CLSM with WPSA can be utilized as sewage-pipe backfill material [ 39 ].…”
Section: Description Of the Articles Presented In The Issuesupporting
confidence: 74%
“…In the study by [ 39 ], the effects of the mixing conditions of waste-paper sludge ash (WPSA) on the strength and bearing capacity of controlled low-strength material (CLSM) were evaluated, and the optimal mixing conditions were used to evaluate the strength characteristics of CLSM with recyclable WPSA. The strength and bearing capacity of CLSM with WPSA were evaluated using unconfined compressive strength tests and plate bearing tests, respectively.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…Moreover, because incineration ash usually exhibits pozzolanic activity, other types of incineration ash have also been applied as SCMs for CLSM production. These include incineration sludge ash, such as waste paper sludge ash (WPSA) [16], incineration sludge ash [17], and mixed incineration sludge ash [18]; garbage incineration ash, such as domestic waste incinerator bottom ash [19] and industrial waste incineration bottom ash [20]; and biomass incineration ash, such as wood ash [21], corn straw ash [22,23], rice straw ash [24] and bagasse ash [25]. Among the metallurgical industrial by-products, blast-furnace slag is often used as an SCM for CLSM production, due to its high hydration activity.…”
Section: Clsm Strengthmentioning
confidence: 99%
“…They suggested that expanding the use of unqualified raw materials and man-made waste as secondary raw materials could be one of the most important directions for creating a waste-free process to ensure the most reasonable use of natural resources and reduce the negative impact on environmental conditions. Park and Hong [30] analyzed the influence of the mixing conditions of wastepaper sludge ash (WPSA) on the strength and bearing capacity of controlled low-strength materials (CLSM). The results showed that CLSM and WPSA could be used as backfill materials for sewage pipes, which could ensure higher stability compared with soil backfill.…”
Section: Introductionmentioning
confidence: 99%